Strategies for Reducing Suicide at Railroads: A Scoping Review of Evidence and Gaps - Belur, Pooja; Sherry, Patrick; Rodriguez, Ivan; Kurkure, Chetan; Joshi, Shashank V. (International journal of environmental research and public health, 2024)
This review aims to systematically evaluate existing literature on reducing suicides along railroads, with specific focus on effectiveness, limitations, and research gaps in the current evidence base. Database searches were conducted in PubMed, PsycInfo, Scopus, Embase, and CINAHL covering studies published until 30 November 2024. After screening 623 studies and their references, 51 studies were included; 26 empirically assessed rail-related prevention interventions and 25 provided relevant qualitative insights. Physical barriers like removal of grade crossings, addition of fencing, and platform screen doors (PSDs) showed significant promise. Full-height PSDs eliminated all suicides and half-height PSDs significantly reduced suicide incidence. Fencing was found to be effective but raised concerns about feasibility and must be part of a comprehensive approach to mitigate potential displacement. Safe media reporting was linked to decreased suicides and a reduced risk of contagion, and CCTV monitoring and suicide pits also showed potential but had limited research. Other strategies showed mixed evidence and required additional evaluation. Some studies, particularly on physical barriers, showed possible displacement effects to other stations, highlighting the need for studies larger in geographic and temporal scope. Our findings support certain prevention interventions, but generalizability is limited by scope of research and methodological concerns. Overall, our findings highlight the need for broader, long-term studies to confirm efficacy and establish comprehensive, scalable approaches for policy implementation.